Monitoring and examination of adaptation period of microorganisms in membrane-bioreactor system treating fruit juice industry wastewaters - Demirkol, Guler Turkoglu; Durak, Sevgi Gunes; Ovez, Suleyman; Tufekci, Nese (INDERSCIENCE ENTERPRISES LTD, 2014)
In this study, fruit juice industry wastewaters by using MBR process have been monitored and examined considering effective microorganisms and changes in biodiversity during the treatment period. Microbiological examinations have been carried out using conventional microbiological methods and microscopic observations. Eukaryotic and prokaryotic microorganisms and also floc structure of the activated sludge were identified and characterised. On the other hand, environmental parameters effective on microbial diversity of MBR process treating fruit juice wastewaters have been identified and discussed. Fruit juice wastewaters supported almost all kinds of microorganisms, primarily filamentous fungi Aspergillus spp., and ciliated protozoa Coccidia spp. and eliminated nematodes from the MBR system.
Keywords: Aspergillus spp.; Coccidia spp.; nematodes; filamentous microorganisms; fruit juice wastewater; MBR; microbiological monitoring; ACTIVATED-SLUDGE; MICROBIAL PRODUCTS; Environmental Sciences & Ecology